Advances in Environmental Economics: Analysis and Modelling - Jeroen C.J.M. van den Bergh; Peter Nijkamp (Tinbergen Institute, 1998)
This paper gives a concise overview of environmental-economicanalysis. Important issues and modern developments in the field aresurveyed in a systematic way. Next, the concept of sustainabledevelopment is discussed, as it has dominated environmental economicsfor almost a decade now. In addition, the issue of modelling theinterface of the economy and the natural environment making use ofmaterial balance conditions is examined. The paper concludes with aconsideration of issues of uncertainty in policy analysis andforecasting with particular reference to scenario analysis.
Keywords: 330; Umweltökonomik; Theorie